Peran Moderasi Strategi Bisnis Di Antara Thin Capitalization Rule Dan Penghindaran Pajak - Ranindya Hendrastuti; Eko Ganis Sukoharsono; Syaiful Iqbal (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to analyze the effect of thin capitalization rule on tax avoidance moderated by business strategy. Methodology/approach: The research method used is a quantitative approach with secondary data. Samples were taken using purposive sampling and confirmatory factor analysis result ranking to obtain 30 multinational companies registered on the IDX during the 2014-2019 period excluded multinational companies which are not PMK-169 subject. So, the total observations data is 180. The research analysis techniques using hierarchical regression analysis. Findings: The results showed that business strategy can moderate between thin capitalization rule and tax avoidance. The defender business strategy weakens the negative influence of the Thin Capitalization Rule on tax avoidance, whereas the prospector business strategy strengthens the negative influence of the Thin Capitalization Rule on tax avoidance. Practical implications: The government could consider easing the Thin Capitalization Rule for companies operating in business sectors dominated by prospectors and tightening the rules for companies operating in business sectors dominated by defenders. Originality/value: There are still no research references regarding thin capitalization rule on tax avoidance moderated by business strategy. This research develops previous research by adding business strategy with confirmatory factor analysis in the moderation model.